The Effect of Vitamin C Enriched Pellets on the Erythrocytes Profile Oreochromis niloticus - Athif Amirah Elza; Morina Riauwaty; Henni Syawal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Vitamin C important role in maintaining the body's physiological processes, preserving enzymatic activity in collagen biosynthesis, and also plays a role in wound healing. This study aimed to obtain the best dose of vitamin C enriched pellets on red blood profile and growth of Nile Tilapia (Oreochromis niloticus). The study was conducted from May to August 2019 in the Laboratory of Parasitic and Fish Disease, Fisheries and Marine Faculty, Riau  University. The research method used was the experimental method using a one factor Complete Design (RAL) with five treatment and three replicates. The treatments used were Kn (non-vitamin C enriched pellets and non-infected with Streptococcus agalactiae), Kp (non-vitamin C enriched pellets and infected with S. agalactiae), vitamin C enriched pellets P1(1 g/kg), P2(1.5 g/kg), P3(2 g/kg) and infected with S. agalactiae. Tilapia reared for 46 days by vitamin C enriched pellets, then tested on the 32ndday with S. agalactiae bacteria with a density of 108CFU/mL at a dose of 0.1 mL / head intramuscularly, then the fish were re-maintained until the 46thday. The parameters measured include clinical symptoms, total erythrocytes, hemoglobin, hematocrit, absolute weight and survival. The results showed that the best treatment at P3(2 g / kg) yielded total erythrocytes 243.66 x 104cells / mm3, hemoglobin level 8.66 g%, hematocrit value 32.00%, absolute weight growth 21.20 g, and overall survival is 93.33%.  Keywords : Oreochromis niloticus, Vitamin C, Sterptococcus agalactie, Erythrocytes Profile, Growth